Pengembangan Aplikasi “My Brascho” Untuk Mata Pelajaran Ekonomi di SMA Brawijaya Smart School - Syahrul Munir; Anang Setyo Santoso (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
This study aims to develop an ispring-based learning media which is expected to be a solution in learning economics material for national income according to student needs. The research method used by the researcher is research and development with a 4D model. The subjects in this study were students of class XI economics at SMA Brawijaya Smart School. The instruments used in research and development of this media were observation and questionnaires. Data analysis techniques used in testing learning media by expert validation, media validation, and small group trials. Then the data were analyzed using a descriptive percentage analysis technique. The result of the development is a learning media in the form of an android application that contains four components, namely materials, learning videos, quizzes, and profiles. The results of media and material validation show that the product is categorized as